The role of prenatal choline and its impact on neurodevelopmental disorders - Mujica-Coopman, María F.; Paules, Evan M.; Trujillo-Gonzalez, Isis (Frontiers in Nutrition, 2024)
Extensive evidence demonstrates that prenatal nutrition is crucial for adequate fetal development. Specifically, maternal choline intake plays a significant role in gene expression, epigenetics, and cell membrane formation.Preclinical models have shown that maternal dietary intake improves the development of the cerebral cortex and hippocampus. This review focuses on the role of prenatal choline intake and discusses its potential role in neurodevelopmental disorders especially since choline has emerged as a promising coadjutant to mitigate cognitive and developmental disorders. However, more evidence regarding timing, dosage, and molecular mechanisms is needed. In this review, we discuss the impact of prenatal choline availability, evidence from current models, and gaps to address in how choline may impact the symptomology and manifestation of Rett Syndrome, Fragile X Syndrome, and Down Syndrome. Our ultimate goal is to highlight the importance of choline for maternal health and its potential beneficial impact on neurodevelopmental disorders.